2018
DOI: 10.1016/j.canep.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Portugal: Temporal trends and age-specific incidence by geographic regions

Abstract: The variant patterns observed could be due to a combination of different screening practices and/or exposure to risk factors across regions. Disease heterogeneity among younger and older women may also explain part of the differences in age-specific rates. These results justify continued monitoring of breast cancer incidence by region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The sample's age range was between 28 and 79 years, which aligns with the literature that breast cancer occurs both in younger and older women in Portugal (Forjaz de Lacerda et al, 2018). In this study, the most frequent surgical intervention was mastectomy.…”
Section: Discussionsupporting
confidence: 80%
“…The sample's age range was between 28 and 79 years, which aligns with the literature that breast cancer occurs both in younger and older women in Portugal (Forjaz de Lacerda et al, 2018). In this study, the most frequent surgical intervention was mastectomy.…”
Section: Discussionsupporting
confidence: 80%
“…Eight out of the ten European studies also reported an increase in incidence in women under 50 [ 61 63 , 65 69 ] with two finding no statistical change [ 60 , 64 ]. In Portugal, the magnitude of change was larger than observed in the US and Canada, with APC around 2.7 [ 63 , 66 ], but for the other countries the observed increase was ~1–2% per year.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer incidence is growing all over the world, reflecting the growth and aging of the population and the increase of cancer risk factors (Bray et al, 2018). Breast cancer has proven to be the leading cause of female death worldwide (Ferlay et al, 2015), accounting for almost one in four cancer cases among women, and similar numbers have been found in Portugal (Forjaz de Lacerda et al, 2018).…”
Section: Introductionmentioning
confidence: 95%